LAYANAN BIMBINGAN KLASIKAL TENTANG MOTIVASI BELAJAR PESERTA DIDIK KELAS XI IPS SMA NEGERI 2PONTIANAK - Marini Nurul Hidayah E E; Purwanti Purwanti; Sri Lestari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractQuality education is not enough only through the science of education and technology alone, for that guidance and counseling is tasked with assisting the acquisition of science and technology through education. One service that can be given to students to achieve optimal development in accordance with their potential was classical guidance services. Guidance and counseling services that can help maintain and increase learning motivation, namely classical guidance services because classical guidance activities can help students to get a lot of information from counselors that can be used to help solve problems faced, especially in improving student achievement. A common problem in this study was "What is the Classical Guidance Service About Motivation for Learning for Students in the XI Class of Social Sciences in Pontianak 2 High School?" The method in this study was descriptive and the form of research is a form of study survey. "The population in this study was 180 and a sample of 47 students in class XI IPS at Pontianak 2 High School. Based on the results of planning analysis categorized as" good ", implementation was said to be" good ", evaluation was categorized as" good ", and learning motivation was categorized as" Good " Keywords: Classical Guidance Services, Learning Motivation